Analysis of microbial hydrocarbon degradation using TLC-FID - Cavanagh, JE; Juhasz, AL; Peter Nichols; Franzmann, PD; Thomas McMeekin (1995)
Biodegradation of the hydrocarbons, tetradecane and phenanthrene, by mixed and pure cultures of Antarctic bacteria was measured using thin layer chromatography-flame ionisation detection (TLC-FID). Losses of up to 65% of tetradecane and complete degradation of phenanthrene with concurrent increases in bacterial biomass, measured by polar lipid concentration, were observed. TLC-FID has advantages over other analytical techniques used to monitor hydrocarbon biodegradation by enabling a number of samples to be replicated and run simultaneously in a short period of time. TLC-FID analysis enables three samples to be run in triplicate and analysed in 45 min. Analysis time may be further reduced if only one compound class is present in the samples. The TLC-FID system can detect concentrations as low as 0.1 Î¼g/Î¼l, as applied on the chromarods, with a reproducibility of Â± 10%. Biodegradation of low molecular weight hydrocarbons, while not accurately quantitated using TLC-FID, could be qualitatively assessed using this system.